Bipedicle-Conjoined Deep Inferior Epigastric Perforator Flaps for Unilateral Breast Reconstruction in Overweight and Obese Patients: Do the Benefits Outweigh the Risks? - Sultan, Steven M.; Seth, Akhil K.; Lamelas, Andreas M.; Greenspun, David T.; Erhard, Heather A. (Journal of Reconstructive Microsurgery, 2020)
Background Some surgeons have advocated for the use of bipedicle-conjoined deep inferior epigastric perforator (DIEP) flaps in unilateral autologous breast reconstruction in thin patients in whom a hemiabdominal flap is deemed insufficient. There have been no studies to date, however, exploring complication rates for bipedicle-conjoined DIEP flaps for unilateral reconstruction in overweight or obese patients.Methods The authors performed a retrospective review of two senior authors' patients from 2013 until 2018. In this time period, 71 patients underwent unilateral breast reconstruction with bipedicle-conjoined DIEP flaps. The patients were divided into normal weight (body mass index [BMI] < 25, n = 30), and overweight/obese (BMI > 25, n = 41) groups. Outcomes were reviewed for both major and minor complications.Results The average BMI of the normal group was 23.1 ± 1.3 kg/m2, while the average BMI of the overweight/obese group was 28.9 ± 4.0 kg/m2 (p < 0.01). There were no significant differences in demographics or comorbidities between the two groups.There were no statistically significant differences in the overall incidence of major or minor complications between the two groups (major: overweight/obese = 12.1%, normal BMI = 10.0%, p = 0.39; minor: overweight/obese = 39.0%, normal BMI = 36.7%, p = 0.47). The rate of moderate fat necrosis was significantly higher in the overweight/obese group (overweight/obese = 9.8%, normal BMI = 0%, p = 0.04).Conclusion Unilateral breast reconstruction with bipedicle-conjoined DIEP flaps can be performed safely in overweight and obese patients. The use of bipedicle-conjoined DIEP flaps in this population allows surgeons to provide overweight or obese patients with reconstructions that are commensurate with their body habitus and/or contralateral breast.
Keywords: breast reconstruction; stacked flaps; deep inferior epigastric perforator microsurgery